MENGGESER TITIK FOKUS LENSA PLASMONIK SPIRAL DENGAN MENGUBAH PANJANG GELOMBANG CAHAYA DATANG - Oktafiani, Fitri (Sekolah Tinggi Teknologi MIGAS, 2024)
Plasmonic structures are metal-based structures characterized by plasmon oscillations in the electron conduction band in response to external radiation. This structure has strong light absorption and light scattering as well as electromagnetic field amplification at short distances (near-field). Based on these advantages, improving the focusing performance of surface plasmonic polariton waves is urgently needed. The sharp focus with strong intensity has been used for various applications, including nanoimaging, nanolithography, and optical tweezers. In this research, we use a spiral plasmonic lens combined with a groove ring and the incident beam has a circular polarization direction (circular polarization). The spiral plasmonic lens functions to generate plasmonic waves, while the groove ring functions to spread plasmonic waves on the surface to the focal point with a certain curve in the z-axis direction (far-field). Parameter optimization is carried out by varying the position of the ring groove. Two waves are used to shift the focus point, namely 1064 nm and 1280 nm. The focal point experiences a range of +500 nm on the z-axis when the waveform is changed. However, the intensity of the focal point at the 1280 nm wave is lower than at the 1064 nm wave. This is in accordance with the theory that when the focal point is further away from the surface structure, the intensity decreases. Shifting the focal point by changing waves can be used in several applications, one example is for manipulating microparticles in two different places.